The Foundation And Development Of Batman City - Sunkar, Murat; Tonbul, Sadettin (Istanbul Univ, Fac Letters, Dept Geography, 2010)
Batman, which is located in the Southeastern Anatolia Region of Turkey, is a medium-sized city that has rapidly developed within the last five decades thanks to petroleum extraction and thus gained the status of a province. Batman, once a small village called Iluh before 1950, started to develop with the extraction of petroleum on Mountain Raman and the establishment of modern oil refinery in 1966. It is one of the model cities that have rapidly developed in the process of urbanization in Turkey after 1970. Rapid urbanization movements in Batman came about in specific periods. Petroleum extraction and establishment of an oil refinery played a considerable role in the development of Batman city until 1990, and after this period, migrations from rural areas especially due to terrorist actions had an effect in the development process of the city. In this study, considering specific periods with regards to population growth, the foundation and development process of Batman city was evaluated in five different periods including the period till 1955, the development periods from 1955 to 1980, from 1980 to 1990, from 1990 to 2000 and from 2000 to 2010.
Keywords: Batman city; Urbanization; Petroleum; Iluh; Mountain Raman